A Comparative Psycho-Sociolinguistic Overview of The Phonemic Realizations of The Letter <Ee> in (Nigerian) English As A Second Language (ESL) and Received Pronunciation (RP) - Ekundayo, Omowumi Bode Steve (IJLECR (International Journal of Language Education and Cultural Review), 2016)
This paper examines the articulation of the letter <Ee> in Educated Nigerian English (ENE) against the psycho-sociolinguistic background of English as a Second Language (ESL), the concepts of interference and intraference. Examples were gathered from 2005 to 2013 through unstructured interviews, participant and non-participant observation, and the recording of spontaneous speech. Methods of data analysis are qualitative and quantitative. The ordinal data are presented in percentile and frequency tables and charts and the linguistic texts are described and explained. The study established that as a result of intraference, educated Nigerians mix up the various RP realizations of the letter <e>. As the articulations examined here are institutionalized in ENE and as they have both national and international intelligibility, it is proposed that they be treated as variations that typify ESL varieties.